Las remesas de los inmigrantes en España: factores y estrategias - Roquero, Esperanza (Política y Sociedad, 2008)
Global amount of remittances from migrants to their original countries has increased in the last few years. Drawing on the international literature on remittances from migrants, we review the most relevant theoretical approaches and empirical researches applied on this subject in some parts of the world. According to the few studies carry out in Spain, this essay highlights some relevant questions and issues focusing on the phenomenon of market of remittances.